LEGAL REVIEW OF DISHARMONIZATION OF REGIONAL REGULATIONS IN MAGELANG REGENCY (Study of Regional Regulation Number 2 of 2013 Concerning Livestock Business) - Ikrar Prasetya, Tabah; Hafidz, Jawade (Jurnal Hukum Khaira Ummah, 2023)
The 1945 Constitution of the State of the Republic of Indonesia authorizes local governments to organize and manage their own governmental affairs according to the principle of autonomy and co-administration. Implementation of local government in carrying out its duties, authorities, obligations and responsibilities under higher legislation may establish regional policies formulated in regional or local regulations. Such regional policy shall not be contrary to the higher laws and regulations and the public interest and other regional regulations. Local Government of Magelang Regency has a regulation regulating the implementation of Livestock Business namely Regional Regulation No. 2 of 2013 on Livestock Business (Lembaran Daerah Magelang Regency Year 2013 Number 2). However, there is disharmonization with other laws and regulations that are equal. There are several articles in Regional Regulation No. 2 of 2013 on Livestock Businesses that are not in harmony with other Regional Regulations resulting in disharmonization. The need for harmonious and integrated legislation is an indispensable requirement for the realization of order, ensuring legal certainty and protection. Efforts that can be done to overcome disharmonization of a legislation such as, namely; To revoke certain articles that have disharmony or all articles of legislation in question by the institution / institution authorized to form it, to submit a judicial review request to the judiciary, to ensure that the process of formulating the law shall be conducted in accordance with the principle of legal certainty, harmonization , Rounding, consolidation of the conception of the draft Local Regulation, is an attempt or process to realize harmony, conformity, harmony, suitability and balance among various elements in drafting the draft Law as a unanimity of a whole, compact or solid idea as an integral part of the whole system Hierarchically arranged legislation.Keywords: Disharmonization, Regional Regulation on Livestock Businesses of Magelang, Efforts to prevent disharmony